Dyslipidemia in Patients of Diabetic Nephropathy - Tasnim, Sayeem; Dutta, Pradip Kumar; Alam, ASM Towhidul; Haque, Mahmudul (Journal of Chittagong Medical College Teachers’ Association, 2012)
Background and Aims: Diabetic nephropathy (DN) is one of the leading causes of end stage renal disease (ESRD). Dyslipidaemia is common in both dialysis and non-dialysis populations. Dyslipidaemia is also one of factors for progression of chronic kidney disease (CKD). Besides Dyslipidaemia is also responsible for premature atherosclerosis which increases cardiovascular morbidity in CKD patients. This study is aimed at to show patterns of Dyslipidaemia in overt diabetic nephropathy pts admitted in Nephrology Department of Chittagong Medical College. Materials and Methods: It is a cross-sectional case-control study. Sixty six diabetic patients with mean age 49.5± 11 years with serum creatinine > 1.5 mg% and urinary total protein (UTP) > 500mg/day were enrolled as cases and thirty three diabetic patients with mean age 43.5± 8.9 years with serum creatinine < 1.5 mg% and UTP <500mg/day were included as controls. Results: Majority (92.4%) of patients in case group had Dyslipidaemia compared to 23.3% of the patients in control group (p<0.001). The level of serum total cholesterol, triglyceride and LDL cholesterol were significantly higher in case group than those in control group (227.0 ± 76.2 vs. 176.3 ± 23.4 mg/dl, p <0.001; 230.1 ± 80.0 vs. 134.8 ± 40.4, p<0.001 and 132.6 ± 73.6 vs. 99.7 ± 23.6, p=0.001). The serum HDL was almost comparison of similar in both groups (49.1±8.1 vs. 47.7 ± 12.4) (p=0.509). Presence of raised triglyceride was 41- fold (95% CI = 9.52 – 177.39) higher in diabetic patients with nephropathy than that in diabetic patients without nephropathy (p<0.001). Conclusion: Serum triglyceride was observed to be independently associated with the development of diabetic nephropathy. Lipid-lowering therapy is, therefore, essential to control dyslipidaemia in order to reduce the incidence of diabetic nephropathy along with the prevention of early atherosclerotic cardiac diseases. JCMCTA 2011; 22(2): 12-16